Evaluasi Kebijakan Penanggulangan Bencana (Studi Pada BPBD Kabupaten Kediri) - Fitrianto, Mochamad Rizki (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
Kediri Regency is one of the regions in the province of East Java with various potential natural disasters except tsunami. Some potential natural disasters in Kediri Regency are volcanic eruptions, floods, landslides, nipples, earthquakes. Referring to the IRB (Disaster Risk Index) released by BNPB in 2013, shows that Kediri regency is included in one of the administrative areas in East Java that has a high disaster index. The policy on disaster relief in Kediri Regency has been arranged in regional regulation No. 2 year 2015 which governs the Organization and administration of BPBD (Regional disaster management Agency). The policy has been running for almost 5 years, therefore seeing the various potential disasters owned by Kediri district, researchers want to examine the extent to which the policy has been implemented and observe about readiness in the face of various potential future threats in the future. The findings in the field indicate that in implementing a disaster policy there are currently some indicators in the evaluation (Dunn, 1999) that has not been achieved optimally.